Dyspnoea at Term in an Obese Mother. (22nd September 2011) - O'Dwyer, Vicky; O'Brien, Yvonne; Farah, Nadine; Turner, Michael J.
Abstract : Peripartum cardiomyopathy is a serious, potentially life-threatening heart disease of uncertain aetiology in previously healthy women. We report a morbidly obese woman who presented with peripartum shortness of breath. We discuss the differential diagnosis of dyspnoea in pregnancy and highlight the complexity of care of the morbidly obese woman.